Character-Oriented Development of Accounting Teaching Materials and Higher Order Thinking Skills (HOTS) - Mariati Mariati; Uun Ahmad Saehu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to develop HOTS-oriented assessment instruments in the form of books and guidebooks for developing HOTS-oriented teaching materials for prospective accounting teachers who are still in semester II to semester IV in the Accounting Education Study Program as well as for teachers and lecturers who teach subjects / subjects. accounting courses. This research is a research and development (R&D) which is adapted from the ADDIE development model. There are 5 stages: 1)Analysis, 2)Design, 3)Development, 4)Implementation, and 5)Evaluation. The assessment instrument developed contains three cognitive domains. covering aspects of analysis (C4), assessing/evaluating (C5) and creating/creating (C6). The results showed that the teaching materials produced were valid, practical, and effective in terms of the orientation of the teaching materials towards character and HOTS. assessment results through a character questionnaire and HOTS test. Based on the results of the assessment, the percentage of students with at least good character increased from 78% to 100% (an increase of 22%). Furthermore, based on the HOTS test results, the number of students who completed increased from 0% to 74 % (an increase of 74%).